Magnetic Resonance Imaging (MRI) Technology in the Diagnosis of Rectal Cancer - Kozarenko, Tetyana; Dyminskyi, Oleksandr; Zvyrych, Vitalii (The Ukrainian Scientific Medical Youth Journal, 2025)
The article is devoted to the study of the use of magnetic resonance imaging technology (MRI) in the diagnosis of rectal cancer, which is an important stage in modern cancer. The purpose of the article is to carry out a systematic review of scientific sources that highlight the effectiveness of MRI in determining the stage of the tumor process, evaluation of lesions of lymph nodes and accuracy in planning treatment approaches, in particular surgery. The task is to analyze the accuracy of modern MRI methods for the diagnosis of rectal cancer and to consider technological solutions to improve MRI in the diagnosis of rectal cancer. A comprehensive analysis of publications in databases such as Google Scholar, PubMed, Scopus and IEEE XPlore was conducted on the basis of scientific research. The data revealed is systematized to highlight key technical and clinical aspects that require further development. The main attention is paid to the methods of contrast enhancement and diffusion-weighted MRI, which showed a high level of sensitivity (90-95%) and specificity (85-90%) in the detection of tumor invasion and metastases into lymph nodes. The advantages of methods that allow to accurately evaluate the blood supply to the tumor and the invasiveness of the process are considered, which is especially important for choosing the appropriate treatment tactics. Analysis of scientific works indicates that 1) MRI, due to high accuracy and safety, plays a key role in determining the localization and stage of the tumor process and is an indispensable method of diagnosis of rectal cancer, which provides accurate visualization Treatment and reduces the risk of relapse; 2) Modern MRI methods show high accuracy in the diagnosis of rectal cancer. In particular, highly separated MRI and dynamic contrast MRI have high sensitivity (90-95%) and accuracy (90%), which makes them effective for preoperative stages and tumor invasion. MRI with diffusion-weighted images also has high sensitivity and is useful for evaluating the response to therapy, which is important for monitoring the progress of the disease; 3) methods of contrast enhancement and advanced analysis of images significantly increase the accuracy of diagnosis, especially when predicting the effectiveness of neoadjuvant therapy; 4) there is a need to further improve MRI methods to reduce the frequency of false positive results in the early stages, which will improve the quality of treatment and increase the life expectancy of patients. 5) The development of artificial intelligence and the use of combined methods of diagnosis, in particular with other visualization technologies, will significantly increase the accuracy and availability of MRI in cancer diagnosis.